Faktor-Faktor yang Berhubungan dengan Terjadinya Baby Blues Syndrome pada Ibu Post Partum: Factors Related to the Incidence of Baby Blues Syndrome Among Postpartum Mothers - Yolanda, Helen; Sumarsih; Riska Hediya Putri; Palupi, Rini (Journal of Nursing Education and Practice, 2024)
Introduction: The postpartum period is the time experienced by every woman after giving birth. The impact of postpartum blues (baby blues) on infants can hinder their growth and development, leading to issues such as language delays and low IQ. Several risk factors for postpartum blues include age, parity, pregnancy status, and support from husbands and families. The global prevalence of postpartum blues ranges from 3% to 8%, while in Lampung, 14.6% of mothers experience postpartum blues. Based on the results of a pre-survey conducted in Airan Raya during June 2024, it was recorded that 63 mothers experienced postpartum blues. Objectives: The aim of this study is to identify the factors associated with the occurrence of postpartum Baby Blues Syndrome among postpartum mothers at Airan Raya Hospital. Method: This study employs a quantitative method with a cross-sectional approach using interviews and observations through questionnaires. The population in this study were postpartum mothers. The subjects are postpartum mothers from May to June 2024 at Airan Raya Hospital, with a total of 63 postpartum mothers and a total sampling technique, resulting in 63 respondents. Data analysis was conducted using the Chi-Square test. Result: The results of the study showed a relationship between age and the incidence of postpartum blues syndrome with a p value of 0.001, a relationship between parity and the incidence of postpartum baby blues syndrome with a p value of 0.001, a relationship between pregnancy status and the incidence of postpartum baby blues syndrome with a p value of 0.007, and a relationship between husband's support and the incidence of postpartum baby blues syndrome with a p value of 0.063. Conclusion: There is a relationship between age, parity, pregnancy status and husband's support with the incidence of postpartum blues syndrome.